Iman, Harapan, dan Kasih: Kekuatan dalam Kerapuhan Manusia Menghadapi Pandemi Covid-19 - I Ketut Gegel (Sekolah Tinggi Widya Sasana, 2021)
This article intends to unravel the power of faith, hope and love in dealing with human weaknesses in facing Covid-19 pandemic. This epidemic has disrupted the order of human life as a whole, both private and public. The government has responded by seeking various things, starting from implementing physical distancing policies up to implementing the limitation of community activities. In addition, vaccination activities continue to be intensified. The purpose of all this is to slow down the pace of the Covid-19 pandemic. We have to appreciate these efforts. From the other side, we realize that to solve this problem we cannot rely merely on government efforts. The community must play an active role. In addition to complying with health protocols, the self-quarantine sought by community needs to be appreciated. However, these efforts need to be accompanied by strengths which come from within humans, namely faith, hope and love, as a complement to these external efforts. To describe this problem, the author uses qualitative research methods. The author studied a number of articles, such as Joerg Rieger, Hope versus Hope: Confronting Despair in Ancient and Present Times (2020); J.M. Child, Truth, Hope, Compassion in Times of Corona Virus and Presidential Elections (2020); and other documents related to this research. The results of this study confirm that the strength of the inner human forces altogether with solidarity performed by community can help to overcome the Covid-19 outbreak.